2021
DOI: 10.3390/nu13031008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Short-Term Consumption of Hericium erinaceus on Serum Biochemical Markers and the Changes of the Gut Microbiota: A Pilot Study

Abstract: Hericium erinaceus (H. erinaceus) is widely studied as a medicinal and edible fungus. Recent studies have shown that H. erinaceus has protective effects for diseases, such as inflammatory bowel disease and cancer, which are related to gut microbiota. To investigate the benefits of H. erinaceus intake on gut microbiota and blood indices in adulthood, we recruited 13 healthy adults to consume H. erinaceus powder as a dietary supplement. Blood changes due to H. erinaceus consumption were determined by routine hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
4
17
0
3
Order By: Relevance
“…The data of α diversity indicate that HEPs can increase the bacterial richness and diversity of male fecal fermentation broth and increase the bacterial diversity of female fecal fermentation broth. This is consistent with population studies which state that daily H. erinaceus supplementation increases the Alpha diversity within the GM community ( 20 ). According to the previous research data of the population, the richness of the bacterial community is closely linked to obesity, e.g., obese individuals had lower bacterial abundance and gained more weight over time ( 45 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The data of α diversity indicate that HEPs can increase the bacterial richness and diversity of male fecal fermentation broth and increase the bacterial diversity of female fecal fermentation broth. This is consistent with population studies which state that daily H. erinaceus supplementation increases the Alpha diversity within the GM community ( 20 ). According to the previous research data of the population, the richness of the bacterial community is closely linked to obesity, e.g., obese individuals had lower bacterial abundance and gained more weight over time ( 45 ).…”
Section: Discussionsupporting
confidence: 92%
“…At the genus level, the results of the present study are consistent with in vivo studies in animals and human studies that H. erinaceus extracts or daily H. erinaceus supplementation could promote relative abundances of beneficial GM, e.g., Bifidobacterium , Lactobacillus, Faecalibacterium , and some SCFA-producing bacteria, and downregulated some pathobionts ( 19 , 20 ). Bifidobacterium is a key symbiotic bacterium that plays a dominant role in human intestines.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recent studies have reported that the genus Gemmiger was mentioned in research on the influence of Hericium erinaceus on the intestinal flora. In a study, it was found that this genus was correlated with clinical indicators such as uric acid in patients [ 21 ]. This result is similar to the results of our study, suggesting that Gemmiger is related to uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are many research reports on the genus Clostridium . In China, some researchers have applied Clostridium to carry out animal experiments on hyperuricemia model mice, which proved that this bacteria had a certain improvement effect on uric acid levels [ 21 ]. In combination with the existing studies, we consider the genus Clostridium with great potential to become a new generation of probiotics.…”
Section: Discussionmentioning
confidence: 99%